Elements of Context in Speech on the Youtube Channel Podcasts: Cyberpragmatics Perspective - Dewi Puji Lestari; Anang Santoso; Gatut Susanto (Graduate School of Universitas Negeri Malang, 2023)
The purpose of this study is to describe the elements of context in speech in a cyberpragmatics perspective. This research approach is qualitative with virtual ethnographic type research. The research data is in the form of snippets of dialogue/conversations in podcasts. Meanwhile, the data source is a transcribed video podcast. The data was collected using the free-to-talk method and tapping techniques. This study uses Miles and Huberman's theory of activity flow data analysis and uses Dell Hymes' SPEAKING theory. This study found eight elements of context in the speech data. The elements are setting and scene, participants, purpose, act sequence, key, instrumentalities, norms of interaction and interpretation, and genre.